2021
DOI: 10.1101/2021.04.02.438193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benchmarking scRNA-seq imputation tools with respect to network inference highlights deficits in performance at high levels of sparsity

Abstract: Gene correlation network inference from single-cell transcriptomics data potentially allows to gain unprecendented insights into cell type-specific regulatory programs. ScRNA-seq data is severely affected by dropout, which significantly hampers and restrains current downstream analysis. Although newly developed tools are capable to deal with sparse data, no appropriate single-cell network inference workflow has been established. A potential way to end this deadlock is the application of data imputation methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
(72 reference statements)
1
6
0
Order By: Relevance
“…In agreement with previous studies, we see that imputation may boost gene-gene correlations in a questionable way, thereby introducing FP edges in a network. 23,37 Steinheuer et al 37 evaluated the impact of data imputation on network inference via a gene correlation analysis using simulated data. There, the authors downsampled bulk RNA-seq data, applied imputation methods, and compared the gene module preservation and edge recovery upon imputation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with previous studies, we see that imputation may boost gene-gene correlations in a questionable way, thereby introducing FP edges in a network. 23,37 Steinheuer et al 37 evaluated the impact of data imputation on network inference via a gene correlation analysis using simulated data. There, the authors downsampled bulk RNA-seq data, applied imputation methods, and compared the gene module preservation and edge recovery upon imputation.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous studies, we see that imputation may boost gene-gene correlations in a questionable way, thereby introducing FP edges in a network. 23 , 37 Steinheuer et al. 37 evaluated the impact of data imputation on network inference via a gene correlation analysis using simulated data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…does not improve the network inference precision over downsampled data (Supplemental Figures 3(C),(G),(K), 4(C),(G) and 5(C),(G)), unlike what was reported in the aforementioned study where the authors observed that combining SAVER and GENIE3 does improve network inference performance in some cases. In [81], it was reported that low capture efficiencies pose a challenge for imputation and network inference methods and that some imputation methods, namely DCA [23], preserve the gene-gene correlations structure even though false positive correlations are introduced, these findings are consistent with our results (Supplemental Figures 3, 4 and 5) where we found that for low capture efficiencies, regardless of the imputation and network inference method, the network inference precision is poor and we also found that SAVER similar to DCA preserves the gene-gene correlations structure as mentioned above.…”
Section: Overall Performance Of Network Inference Algorithms Is Inversely Related To Number Of Combination Reactions Consideredmentioning
confidence: 99%
“…Finally, we compared our results with two recent complementary studies that investigated the impact of imputation on network reconstruction performance [80,81].…”
Section: Overall Performance Of Network Inference Algorithms Is Inversely Related To Number Of Combination Reactions Consideredmentioning
confidence: 99%